Cross-Cultural Study of Entrepreneurship and Ethics Education - Roy, Kavita; Swargiary, Khritish (International Research Journal of Business Studies, 2025)
This mixed-methods comparative study explores entrepreneurship and business ethics education among young adults (20–30 years) in Bangalore, India, and Arizona, USA. Analyzing 200 participants (100 per region) through stratified random sampling, it highlights baseline disparities: Bangalore participants scored lower in entrepreneurial knowledge and ethical understanding compared to Arizona participants. Post-intervention, both groups showed significant improvements, with Bangalore participants experiencing notable gains in ethics knowledge, ethical scenario experience, and practical application interest. Arizona participants also improved ethics knowledge and scenario experience. Employment and socioeconomic differences were statistically significant. Using surveys, interviews, focus groups, and workshops, the study underscores cultural and institutional influences on learning, offering adaptive strategies to harmonize global standards with local contexts in entrepreneurship education.